1988
DOI: 10.1177/08959374880020022401
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoglobulin G Antibody To Periodontal Bacteria

Abstract: The purpose of this study was to assess the serum antibody levels to periodontal bacteria in patients with periodontal disease, and to explore the diagnostic uses of the serum antibody assessment and its potential as a therapeutic guide. One hundred twenty-nine patients were clinically examined for the type and extent of periodontal destruction and serum IgG antibody levels to Actinobacillus actinomycetemcomitans (Aa), Actinomyces israelii (Ai), A. viscosus (Av), Bacteroides asaccharolyticus (Ba), B. corporis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 31 publications
1
84
1
Order By: Relevance
“…In addition to the periodontal examination, a blood IgG antibody titer assay for periodontal pathogens with an enzyme-linked immunosorbent assay (ELISA), as previously described, was used to assess the degree of periodontal disease based on the detection of humoral immunologic responses accompanying the elevation in the serum IgG antibody titers against periodontal pathogens. 11,12 The results showed that the IgG antibody titer against A actinomycetemcomitans Y4, the B strain of A actinomycetemcomitans, which is frequently associated with AgP, was 4.85 times higher than the mean of 2 SD of the values observed in the healthy controls in a previous report (Fig 1, C). 12 The patient was therefore diagnosed with generalized AgP, possibly caused by A actinomycetemcomitans Y4.…”
Section: Diagnosis and Etiologymentioning
confidence: 65%
“…In addition to the periodontal examination, a blood IgG antibody titer assay for periodontal pathogens with an enzyme-linked immunosorbent assay (ELISA), as previously described, was used to assess the degree of periodontal disease based on the detection of humoral immunologic responses accompanying the elevation in the serum IgG antibody titers against periodontal pathogens. 11,12 The results showed that the IgG antibody titer against A actinomycetemcomitans Y4, the B strain of A actinomycetemcomitans, which is frequently associated with AgP, was 4.85 times higher than the mean of 2 SD of the values observed in the healthy controls in a previous report (Fig 1, C). 12 The patient was therefore diagnosed with generalized AgP, possibly caused by A actinomycetemcomitans Y4.…”
Section: Diagnosis and Etiologymentioning
confidence: 65%
“…Besides, from analysis under adjusted age we found that at a cut-off value of 5.04, the groups with a positive plasma IgG titer to P. gingivalis had more significantly individuals showing positive LDL-C levels than groups with a negative IgG titer ( Table 2). Infection with periodontal bacteria leads to humoral immunological responses and elevates the serum IgG antibody levels against periodontal pathogens [16]. Hence, IgG titer to P. gingivalis reflects the host immune response against the pathogen, thus indicating a history of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The role such antibodies may play in the onset and progression of the disease is not totally clear. Periodontal therapy appears to have a marked effect on the humoral immune response to antigens of periodontopathic bacteria Vincent et al, 1987;Murayama et al, 1988). Therapeutic intervention by scaling and root planing or by surgery significantly enhances serum antibody levels and avidities to antigens of P. gingivalis and induces seroconversion in seronegative patients Chen et al, 1991a;Sjostrom et al, 1994).…”
Section: Humoral Immune Response In Patients With Periodontitismentioning
confidence: 94%
“…actinomycetemcomitans antigens in sera of patients with aggressive periodontitis (localized juvenile periodontitis) that was absent from normal subjects (Genco et al, 1980). Many, although not all, patients with periodontitis produce a humoral immune response to periodontal disease-associated bacteria and their antigens during the course of a periodontal infection ( Mouton et al, 1981;Ebersole et al, 1982a,b;Taubman et al, 1982a;Tew et al, 1985;Ebersole et al, 1986;Vincent et al, 1987;Ishikawa et al, 1988;Murayama et al, 1988;Zambon et al, 1988a,b;Ogawa et al, 1990;Chen et al, 1991b;Whitney et al, 1992;Ling et al, 1993). The role such antibodies may play in the onset and progression of the disease is not totally clear.…”
Section: Humoral Immune Response In Patients With Periodontitismentioning
confidence: 95%